Secularisation - Mai, Jianjun (IiUM press, 2024)
Abstract: This article provides a comprehensive overview of secularization, exploring its definition, historical development, and impact on society. Secularization is defined as the process by which religion and religious institutions lose influence in society over time. The article traces the concept's evolution from ancient times through the Enlightenment and into the modern era. It examines secularization theory, which posits that modernization inevitably leads to a decline in religious influence. The theory's core elements of differentiation, rationalization, and worldliness are discussed. Major factors contributing to secularization are analyzed, such as economic development, urbanization, scientific advancement, education, and globalization. The article also presents major critiques of secularization theory, including its lack of empirical support in some contexts, failure to specify causal mechanisms, and oversimplification of the modernization-secularization relationship. Special attention is given to secularization's impact on the Muslim world, highlighting examples from various Muslim-majority countries. The article concludes by exploring the ongoing debates among Muslim scholars regarding secularization and the underlying causes of these differences, which, as pointed out by Syed Muhammad Naquib al-Attas, are the influence of Western ways of thinking among some Muslim scholars and intellectuals.